Learning Choices of Medical Students: An Experience from a Private Medical College in Lahore - Muhammad Sohail Aslam, Asma Siddique, Atika Masood, Neelofar Yousaf Warraich, Misbah-ul-Qamar, Mariam Sheikh (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the patterns of learning methods of undergraduate medical students. Study design: Descriptive cross-sectional study. Place and duration of study: Akhtar Saeed Medical & Dental College, Lahore from 15th November 2022 to 15th January 2023. Methodology: One hundred and six undergraduate medical students, comprising 54 males and 52 females. The questionnaire consisted of 16 items that identified four distinct learning choices: visual, aural, reading/writing and kinesthetic. Results: 14.33% students learned by seeing; 26.59%studied by hearing; 19.16%learned by reading/writing and 19.10% students liked to study by using physical methods.16.39% of students used bimodal sensory modalities and only 4.42% used more than one sensory modality for learning. The results of the study will help medical teaching faculty to modify their educational strategies in response to learning methods of their students. Conclusion: The valuable insight into students’ various approaches to learning and will help teachers to modify their teaching strategies. Keywords: Learning choices, VARK questionnaire, Medical students, Teaching strategies